On Semantic Features of Nomination in New Zealand Prison Jargon (by Example of Lexical-Semantic Group “Prisoner”) - S. S. Trifanova (Научный диалог, 2018)
The semantic features of the nomination in the New Zealand prison jargon are considered on the example of the lexical-semantic group “prisoner.” The relevance of the work is due to the increased interest in the study of social variants of the language in general, and their linguistic features, in particular. Semantic analysis of the studied units assumes their description in two planes - semasiological and onomasiological. Within the framework of semasiology, the organizational structure of the group is analyzed, its synonymic series and sub-standard lexemes in their relation to literary equivalents. In the context of onomasiology the ways of nomination of lexemes are investigated. The principles of two opposite directions for complex semantic description of nominative features of language units are revealed and systematized. The combination of two approaches makes it possible to reflect the organization of the lexical-semantic group under study in the most complete way, taking into account its structure-forming components, and to reveal the mechanisms of naming. It is found that the feature typical to this group is excessive variability, which is functionally determined and manifests itself in the presence of synonymous series. It is noted that the centres of attraction are the objects or phenomena most important for a particular social group. The presented scheme of the analysis of the lexico-semantic group “prisoner” is applicable in the description of other similar paradigmatic groups of the language substandard.